Exchange Rate Volatility and International Trade Flows: Evidence from Thailand - Dau, Mai Lien Thi; Sethapramote, Yuthana (Journal of Applied Economics and Management Strategy, 2021)
ABSTRACT The paper examines the impact of exchange rate volatility on bilateral imports and exports between Thailand and its top-20trading partners from 1996 to 2018 using the autoregressive distributed lag (ARDL) bounds testing approach. Our empirical results show three main findings. First, exchange rate volatility was found to have a significant effect on Thailand’s trade with most countries in the Asia-Pacific region. Secondly, exchange rate volatility mostly had a positive effect on Thailand’s bilateral trade in the short run; however, these effects were found to be negative in the long run. Finally, exchange rate volatility generally was seen to have a slightly stronger effect on imports rather than exports in both the short and long run. This implies that Thai imports show a greater response to exchange rate volatility than Thai exports.